THE IMPACT OF SALE PROMOTION ON IMPULSE BUYING BEHAVIOUR AMONG MUSLIM CREDIT CARD HOLDERS IN MALAYSIA - Siti Hajar Salwa Ahmad Musadik; Ilhaamie Abdul Ghani Azmi, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Studies pertaining to impulse buying have been substantially conducted in developing countries. Nevertheless, such studies are in scarcity amidst Asian countries, particularly Malaysia. Besides, studies that have looked into the variables of sale promotion is also rather sparsely carried out in the light of impulse buying behaviour. As such, this study examined the correlations between sale promotion on impulse buying behaviour among Muslim credit cardholders in Malaysia. In terms of instrument development, this study instrument adopted and adapted from prior studies. Questionnaires were distributed to 1,000 Muslim credit cardholders in Malaysia via purposive and snowball sampling techniques, wherein only 635 were usable for final data analysis. The analysis was performed via Partial Least Square (PLS-SEM) analysis. The outcomes revealed that sale promotion displayed significant positive correlations with impulse buying behaviour.